Towed passive acoustic monitoring complements visual survey methods for Heaviside's dolphins Cephalorhynchus heavisidii in the Namibian Islands Marine Protected Area. Issue 4 (1st October 2020) - Gridley, T; Martin, MJ; Slater, J; Roux, J-P; Swift, RJ; Elwen, SH
Abstract : The genus Cephalorhynchus contains four dolphin species, of which three are classified as Near Threatened or Endangered and one subspecies is close to extinction. Understanding the species' abundance, distributions and habitat preferences is necessary for effective management to prevent further population declines. Heaviside's dolphin C. heavisidii is endemic to the Benguela ecosystem off southwest Africa, and like other Cephalorhynchus species these dolphins produce narrowband high-frequency (NBHF) echolocation clicks with a centroid frequency around 125 kHz. We conducted dedicated visual and acoustic line-transect surveys within and adjacent to the Namibian Islands Marine Protected Area in 2012–2014. Acoustic data were processed in the passive acoustic monitoring software PAMGuard, using the default porpoise click detector and classifier to identify NBHF echolocation clicks. Click detection and classification in PAMGuard included a large excess of false positives, which were easily identified by manual verification of events, and ultimately provided 52 definite detections. The acoustic methods provided data in offshore areas and during overnight periods, but were imperfect and not suitable for ecologically important shallow coastal areas. While demonstrating the utility of passive acoustic monitoring in line-transect surveys targeting Cephalorhynchus species, the study shows that both visual and acoustic methods were needed to collect data throughout the range of Heaviside's dolphin.